Clinicopathological differences between Bartonella and other bacterial endocarditis-related glomerulonephritis – our experience and a pooled analysis - Kitamura, Mineaki; Dasgupta, Alana; Henricks, Jonathan; Parikh, Samir V.; Nadasdy, Tibor; Clark, Edward; Bazan, Jose A.; Satoskar, Anjali A. (Frontiers in Nephrology, 2024)
Background Although Staphylococcus aureus is the leading cause of acute infective endocarditis (IE) in adults, Bartonella spp. has concomitantly emerged as the leading cause of “blood culture-negative IE” (BCNE). Pre-disposing factors, clinical presentation and kidney biopsy findings in Bartonella IE-associated glomerulonephritis (GN) show subtle differences and some unique features relative to other bacterial infection-related GNs. We highlight these features along with key diagnostic clues and management approach in Bartonella IE-associated GN. Methods We conducted a pooled analysis of 89 cases of Bartonella IE-associated GN (54 published case reports and case series; 18 published conference abstracts identified using an English literature search of several commonly used literature search modalities); and four unpublished cases from our institution. Results Bartonella henselae and Bartonella quintana are the most commonly implicated species causing IE in humans. Subacute presentation, affecting damaged native and/or prosthetic heart valves, high titer anti-neutrophil cytoplasmic antibodies (ANCA), mainly proteinase-3 (PR-3) specificity, fastidious nature and lack of positive blood cultures of these Gram-negative bacilli, a higher frequency of focal glomerular crescents compared to other bacterial infection-related GNs are some of the salient features of Bartonella IE-associated GN. C3-dominant, but frequent C1q and IgM immunofluorescence staining is seen on biopsy. A “full-house” immunofluorescence staining pattern is also described but can be seen in IE –associated GN due to other bacteria as well. Non-specific generalized symptoms, cytopenia, heart failure and other organ damage due to embolic phenomena are the highlights on clinical presentation needing a multi-disciplinary approach for management. Awareness of the updated modified Duke criteria for IE, a high index of suspicion for underlying infection despite negative microbiologic cultures, history of exposure to animals, particularly infected cats, and use of send-out serologic tests for Bartonella spp. early in the course of management can help in early diagnosis and initiation of appropriate treatment. Conclusion Diagnosis of IE-associated GN can be challenging particularly with BCNE. The number of Bartonella IE-associated GN cases in a single institution tends to be less than IE due to gram positive cocci, however Bartonella is currently the leading cause of BCNE. We provide a much-needed discussion on this topic.